1991
DOI: 10.1212/wnl.41.6.862
|View full text |Cite
|
Sign up to set email alerts
|

Cortical blindness and residual vision

Abstract: We studied 12 patients with static cortical blindness to evaluate residual vision after destruction of area 17 and to assess the visual capacity of the subcortical "second" visual system in humans. In each case, the cause was bilateral infarction of the occipital lobes. Five patients had total blindness, and four had residual rudimentary vision (RRV), characterized by homonymous areas of light perception in the peripheral field and ability to detect moving objects. Only three patients had the ability to read; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 0 publications
2
34
1
Order By: Relevance
“…8 Whether or not a patient has blindsight appears to depend on the amount of occipital cortex spared, a total lesion of occipital cortex leading to total blindness. 9 However, what is interesting is that, although blindsight patients can 'see' in a rudimentary way, they are not consciously aware of having seen anything at all. The magnocellular pathways that project to the superior colliculus and then to extrastriate cortical areas via the pulvinar are commonly assumed to mediate blindsight-type responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Whether or not a patient has blindsight appears to depend on the amount of occipital cortex spared, a total lesion of occipital cortex leading to total blindness. 9 However, what is interesting is that, although blindsight patients can 'see' in a rudimentary way, they are not consciously aware of having seen anything at all. The magnocellular pathways that project to the superior colliculus and then to extrastriate cortical areas via the pulvinar are commonly assumed to mediate blindsight-type responses.…”
Section: Discussionmentioning
confidence: 99%
“…10 That such a pathway may exist in the human brain and that signals presented in the blind field actually reach the cortex is suggested by evidence which shows that, when visual stimuli are presented to the blind field of blindsight patients, evoked potentials can be picked up directly from the cortex. 9 It is essential that good fixation is maintained during visual field testing, and one of the weaknesses of the FDT test in the screening mode is that fixation is only tested 3 times during the test. Poor fixation during testing could account for the fact that FDT stimuli could apparently be seen by the blind hemifield.…”
Section: Discussionmentioning
confidence: 99%
“…156,157 Although the mechanism of Riddoch's phenomenon is not established, it has been attributed to either preserved islands of visual function within the striate cortex 158 or extrastriate systems bypassing the injured visual cortex. 157,159 The latter explanation seems to have recently gained support from experimental findings. In any case, although the Riddoch phenomenon is of interest, it has never been suggested that it accounts for significant useable visual function following visual cortex injury in adults.…”
Section: Mechanisms Of Visual Recovery In Children With Cortical Visumentioning
confidence: 86%
“…163 The original studies were criticized by some authorities who felt that the residual visual function reported in these adult patients with striate cortex injuries could be accounted for by residual islands of functioning cortex and/or light scatter during the experiments. 159,164 However, control experiments involving blind spot stimulation 165 as well as improved fixation controls have made these explanations less likely to be valid. 45 Moreover, functional imaging studies of some of these patients have failed to reveal residual striate cortex activity.…”
Section: Mechanisms Of Visual Recovery In Children With Cortical Visumentioning
confidence: 99%
“…However, some "blindsight" patients (Weiskrantz, 1998) retain residual visual abilities such as the ability to make perceptual discriminations or perform associated visuomotor control at better than chance levels, while denying conscious awareness of stimuli in their blind visual fields (Blythe, Kennard, & Ruddock, 1987;Corbetta, Marzi, Tassinari, & Aglioti, 1990;Perenin & Jeannerod, 1975;Perenin, Ruel, & Hecaen, 1980). Several reports suggest that V1 is necessary for conscious visual perception (Celesia, Bushnell, Toleikis, & Brigell, 1991;Merigan, Nealey, & Maunsell, 1993). However, some degraded conscious "blindsight" vision may remain, particularly if structures like the superior colliculus, LGN and extrastriate cortex are not directly affected.…”
Section: Pathways For Visual Motion Perceptionmentioning
confidence: 99%